2016
DOI: 10.1007/s10571-016-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 Regulates Migration, Invasion, and Angiogenesis via p38 MAPK Pathway in Human Glioblastoma

Abstract: Runt-related transcription factor 1 (RUNX1) is essential for the establishment of fetal and adult hematopoiesis and neuronal development. Aberrant expression of RUNX1 led to proliferation and metastasis of several cancers. The aim of the present study was to investigate the role of RUNX1 in migration, invasion, and angiogenesis of human glioblastoma using IL-1β-treated U-87 MG human glioblastoma cells as a model. IL-1β at 10 ng/ml stimulated translocation of RUNX1 into the nucleus with increased expressions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 72 publications
2
35
0
Order By: Relevance
“…Similarly, other study has shown a positive correlation between RUNX1 and the MAPK signaling pathway in cancer [33]. Furthermore, we veri ed that these markers also appear to be neutralizing when RUNX1 overexpression and OPN knockdown coexist.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, other study has shown a positive correlation between RUNX1 and the MAPK signaling pathway in cancer [33]. Furthermore, we veri ed that these markers also appear to be neutralizing when RUNX1 overexpression and OPN knockdown coexist.…”
Section: Discussionsupporting
confidence: 83%
“… 47 , 76 Other inflammatory mediators with known links to RUNX1 include the pro-inflammatory cytokine IL-1β and the transcription factor TGF-β. Treatment of a human glioblastoma cell line with IL-1β was shown to up-regulate RUNX1 expression via the p38 MAPK cascade 77 and TGF-β has been shown to increase RUNX1 expression in a range of cell types including adult hippocampal precursor cells, 78 mesenchymal stem cells, CD4 T cells, and a mouse hepatocyte cell line. 79 , 80 Currently, the effects of these inflammatory mediators on RUNX1 expression in the myocardium remain unknown.…”
Section: Triggers Of Runx1 Expressionmentioning
confidence: 99%
“…Recent report shows that RUNX1 may be a putative molecular target of therapies against glioma metastasis and angiogenesis through the activation of p38 MAPK signaling pathway [21]. We measured the expression level of p38 in DR model and HG cell model.…”
Section: Runx1 Expression Level Was Down-regulated By Inhibiting P38 mentioning
confidence: 99%
“…RUNX3 plays a crucial role in definitive hematopoiesis, differentiation of T-and B-cell lineages, and neuronal development [19,20]. Recent report shows that RUNX1 may be a putative molecular target of therapies against glioma metastasis and angiogenesis that function through the activation of the p38 MAPK signaling pathway [21]. However, the relationship between p38 and RUNX1 in retinal micro-angiogenesis in diabetic retinopathy is still unknown.…”
Section: Introductionmentioning
confidence: 99%